Analisis Pencapaian Maqashid Syariah terhadap Kesejahteraan Dosen Fakultas Syariah Unisba - Muhammad Imamul Akhyar; Sandy Rizki Febriadi; Iwan Permana (UNISBA Press, 2023)
Abctract. The meaning of Welfare in Islam aims to achieve human welfare in a kaffah or comprehensive manner, namely both material welfare, spiritual and moral well-being. The conception of well-being and happiness (falah) actually refers to the purpose of Islamic sharia with the preservation of 5 principles in maqashid shari'ah, namely the preservation of religion (ad-ddin), the preservation of the soul (an-nafs), the preservation of reason (al-aql), the preservation of offspring (an-nasl) and the preservation of treasures (al-mal). Maqashid sharia itself is the purposes of sharia and the secrets intended by Allah Almighty in every law of His entire law. So that in order to realize welfare itself, the five main elements must be maintained and realized. The purpose of this study is to describe the concept of maqashid sharia in realizing welfare as well as to find out the analysis of the achievement of sharia maqashid on the welfare of lecturers of the Faculty of Sharia UNISBA. This research uses a qualitative method with a field approach and the data used are primary data obtained directly from the interviews of 13 Lecturers of the Faculty of Sharia UNISBA through the purposive sampling method. The result of this research is that every Lecturer of the Faculty of Sharia who is a sample has practiced the understanding of maqashid sharia with the preservation of 5 principles so as to achieve welfare and happiness. Abstrak. Makna Kesejahteraan dalam Islam bertujuan mencapai kesejahteraan manusia secara kaffah atau menyeluruh, yaitu baik kesejahteraan material, kesejahteraan spiritual dan juga moral. Konsepsi kesejahteraan dan kebahagiaan (falah) sejatinya mengacu pada tujuan syariat Islam dengan terjaganya 5 prinsip dalam maqashid syari’ah, yakni terjaganya agama (ad-ddin), terjaganya jiwa (an-nafs), terjaganya akal (al-aql), terjaganya keturunan (an-nasl) dan terjaganya harta (al-mal). Maqashid syariah itu sendiri adalah tujuan-tujuan syariat dan rahasia-rahasia yang dimaksudkan oleh Allah SWT dalam setiap hukum dari keseluruhan hukum-Nya. Sehingga dalam rangka mewujudkan kesejahteraan itu sendiri, lima unsur pokok tersebut harus dipelihara dan diwujudkan. Tujuan penelitian ini untuk mendeskripsikan konsep maqashid syariah dalam mewujudkan kesejahteraan juga untuk mengetahui analisis pencapaian maqashid syariah terhadap kesejahteraan Dosen Fakultas Syariah UNISBA. Penelitian ini menggunakan metode kualitatif dengan pendekatan lapangan dan data yang digunakan adalah data primer yang diperoleh secara langsung dari hasil wawancara 13 Dosen Fakultas Syariah UNISBA melalui metode purposive sampling. Adapun hasil daripada penelitian ini adalah setiap Dosen Fakultas Syariah yang menjadi sampel telah mengamalkan pemahaman maqashid syariah dengan terjaganya 5 prinsip sehingga tercapainya kesejahteraan dan kebahagiaan.